Investigating atopic dermatitis and evaluating the influence of breastfeeding on infants in South Indian region - Yadav, Preeti K.; Nikhil Deep, Kolanu; Karthiga, Vasudevan; Khan, Shehla Ashraf; Shrivatsam, Paidi; Chand, Purna (International Journal Of Community Medicine And Public Health, 2024)
Background: Atopic dermatitis (AD) is a common inflammatory skin condition affecting infants globally, including in India. Its prevalence is rising, with formula-fed infants showing higher rates than breastfed ones. Breastfeeding provides numerous benefits, including optimal nutrition and immune protection. Although several studies have explored the link between breastfeeding and AD, the evidence is inconsistent. This study aims to assess the prevalence of AD among Indian infants in the Srikakulam region and examine the effect of exclusive breastfeeding (EBF) and formula feeding on AD rates. Methods: This cross-sectional study used convenience sampling to collect data from 180 guardians of infants aged 0-6 months in the Srikakulam region, Andhra Pradesh, from April to June 2024. Data on demographics, feeding practices, and AD diagnoses confirmed by pediatricians were gathered through an electronic questionnaire. Analysis was done using SPSS V.21.0 with chi-square and correlation tests. Results: Among the 180 infants, 72.2% had AD. A significant gender difference was observed, with 85 males and 45 females affected (p<0.05). Most AD cases were found in the 4-8 month age group. EBF was practiced in 30% of infants, while 70% were formula-fed. Formula-fed infants had more hospitalizations. Conclusions: This study shows a high prevalence of AD in the Srikakulam region, with males more affected. EBF may offer protection against severe AD, emphasizing the need for public health efforts to promote EBF. Further research is needed to deepen understanding.